Impact of Pre Loan assessment customer credit worthiness on loan defaults at later stages in Rural Segment – a study at Vehicle Financing NBFC - et. al., Sundar R, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
One of the major issues faced by the financial sector today is the loan delinquencies and loan defaults specifically for NBFC’s in Rural areas. The study conducted with a sample NBFC Mahindra & Mahindra Financial services also struggles with the same issue. The Researcher in this study has tried to find out the methods used by the NBFC for pre loan assessment and the impact of it in controlling the loan defaults at later stages of loan. Mostly these methods help the credit manager identify the suitability of the applicant for loan disbursement, but if these methods have any impact in controlling loan defaults at later stages of loans is an area for study. The data required for this analysis is not available as a published data. Thus it has been collected as Opinion based data from Credit Managers. One sample T test has been applied to statistically analyse the data.